EVALUATION OF FOOD SAFETY IN FOOD AND BEVERAGE ESTABLISHMENTS OF THE COLTA CANTON, CHIMBORAZO PROVINCE (Lex localis - Journal of Local Self-Government, 2025)
Research on food safety in food and beverage service providers in the canton of Colta, province of Chimborazo, is imperative, as these service providers possess limited knowledge regarding food processing, which can compromise the health of national and international tourists visiting the canton's tourist attractions. The objective of this research is to evaluate the relationship between food safety and the culinary practices of food and beverage service providers in the Colta canton, province of Chimborazo, in order to identify its impact on consumer safety and the development of gastronomic tourism. The objective of this study is to examine the present state of food safety in collective food establishments. Key aspects such as good manufacturing practices (GMP), hygiene conditions, compliance with standards according to the Ministry of Tourism, and consumer perception were evaluated. Following a series of descriptive and correlational analyses, it was determined that a significant proportion of establishments did not adhere to the requirements of the Collective Food Industry. The analysis revealed deficiencies in food safety standards, with particular regard to food handling and the sanitary conditions of food preparation and service facilities.